The role of prickle proteins in vertebrate development and pathology - Radaszkiewicz, K A; Sulcova, M; Kohoutkova, E; Harnos, J (Molecular and cellular biochemistry, 2024)
Prickle is an evolutionarily conserved family of proteins exclusively associated with planar cell polarity (PCP) signalling. This signalling pathway provides directional and positional cues to eukaryotic cells along the plane of an epithelial sheet, orthogonal to both apicobasal and left-right axes. Through studies in the fruit fly Drosophila, we have learned that PCP signalling is manifested by the spatial segregation of two protein complexes, namely Prickle/Vangl and Frizzled/Dishevelled. While Vangl, Frizzled, and Dishevelled proteins have been extensively studied, Prickle has been largely neglected. This is likely because its role in vertebrate development and pathologies is still being explored and is not yet fully understood. The current review aims to address this gap by summarizing our current knowledge on vertebrate Prickle proteins and to cover their broad versatility. Accumulating evidence suggests that Prickle is involved in many developmental events, contributes to homeostasis, and can cause diseases when its expression and signalling properties are deregulated. This review highlights the importance of Prickle in vertebrate development, discusses the implications of Prickle-dependent signalling in pathology, and points out the blind spots or potential links regarding Prickle, which could be studied further.
Keywords: Cell Polarity; proteiny s doménou LIM; LIM Domain Proteins; Animals; Signal Transduction; obratlovci; Prickle; lidé; Embryonic development; zvířata; Pathology; polarita buněk; Planar cell polarity (PCP); signální transdukce; Vertebrates; Humans